The effect of inter-repetition rest duration on kinematic and kinetic of snatch - Kevin Tan (2021)
Controlling and manipulation of inter-repetition rest (IRR) could develop diverse levels of fatigueand manifest changes to lifting mechanics. The objective of this study was to examine the effect ofIRR on kinematic and kinetic of snatch lifting during multiple set exercise protocol. Fifteen male(n=15) athletes participated in this study (age = 21.0 1.41 years; body weight = 60.82 2.45 kg; height = 165.70 10.88 cm; snatch one- repetitionmaximum (1RM)/body weight = 0.73 0.117). Session 1 consisted of anthropometric and 1RMdetermination. Sessions 2-4 involved subjects performing 3 sets x 5 repetitions of 85% 1RMwith 10, 30, or 50 seconds of IRR implemented randomly. Joint angle displacement, jointvelocity, ground reaction force (GRF), and barbell velocity (BV) were obtained during eachprotocol using VICON Motion Analysis (100Hz) and AMTI force plate. Repeated measure ANOVA showed significant differences found in ankle, knee and hip jointdisplacement and joints velocity. The barbell velocity showed a significant effect between IRR,(F (2, 28) = 22.831, p <.05), while the maximum vertical GRF showed a significant effect betweenIRR protocols, (F (1.309, 18.323) = 9.953, p = .003). Repeated measure Manova showed asignificant effect of IRR on the maintenance of kinematics and kinetic variables acrossrepetition. BV showed a significant effect of IRR on maintenance of velocity across repetition,(p = .029). However, no significant effect of IRR was observed on the maintenance ofmaximum vertical GRF, (p = .065). Due to the differences found between IRR protocols, theimplementation of IRR may result in an increase or decrease of kinematic and kinetic outputdue to the different levels of fatigue. The implementation of IRR can help to maintainkinematic and kinetic variables which often are affected by neuromuscular fatigue occurred withcontinuousrepetition.